Charge Storage Behaviour of α‐MoO3 in Aqueous Electrolytes – Effect of Charge Density of Electrolyte Cations. Issue 3 (8th February 2022) - Elkholy, Ayman E.; Duignan, Timothy T.; Hussain, Tanveer; Knibbe, Ruth; Zhao, Xiu Song
Abstract: In this paper, we show that the electrochemical performance of α‐MoO3 electrode is significantly dependent on the charge density of three studied aqueous electrolyte cations, i. e. Na +, Mg 2+ and Al 3+ . The charge storage capacity of the α‐MoO3 electrode increases with increasing cation charge density. On the other hand, the initial coulombic efficiency decreases, and the charge transport kinetics are slowed with increasing charge density. This study provides an insightful understanding of the relationship between the charge density of metal ions and their electrochemical behaviour towards α‐MoO3 electrode in aqueous solutions. It also highlights the importance of the appropriate selection of aqueous electrolytes for enhancing electrochemical performance. Abstract : Importance of aqueous electrolytes : The charge storage capacity of layered α‐MoO3 in aqueous electrolytes increases with cation charge density accompanied with decreased initial coulombic efficiency and charge transport kinetics.